2020
DOI: 10.1016/j.envpol.2020.114590
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic concentrations, distributions and bioaccessibilities at a UNESCO World Heritage Site (Devon Great Consols, Cornwall and West Devon Mining Landscape)

Abstract: Devon Great Consols (DGC) is a region in southwest England where extensive mining for Cu, Sn and As took place in the nineteenth century. Because of its historical and geological significance, DGC has protected status and is part of the Cornwall and West Devon Mining Landscape UNESCO World Heritage Site. Recently, the region was opened up to the public with the construction or redevelopment of various trails, tracks and facilities for walking, cycling and field visits. We used portable x-ray fluorescence spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The conversion of mining heritage into productive uses signifies a strategic shift from viewing former mining areas merely as relics to recognizing their potential for fostering activities on previously exploited lands [67]. Bolstered by international initiatives aimed at the redevelopment of these abandoned sites [19][20][21][22][23][24][25], the repurposing of mining heritage into diverse sustainable uses is a burgeoning field. Despite the potential benefits, the transition process is fraught with various hazards and risks, making it imperative to undertake comprehensive risk analyses to navigate the complexities of mining heritage reuse effectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of mining heritage into productive uses signifies a strategic shift from viewing former mining areas merely as relics to recognizing their potential for fostering activities on previously exploited lands [67]. Bolstered by international initiatives aimed at the redevelopment of these abandoned sites [19][20][21][22][23][24][25], the repurposing of mining heritage into diverse sustainable uses is a burgeoning field. Despite the potential benefits, the transition process is fraught with various hazards and risks, making it imperative to undertake comprehensive risk analyses to navigate the complexities of mining heritage reuse effectively.…”
Section: Discussionmentioning
confidence: 99%
“…This innovative reuse not only fosters local economic development but also ensures a sustainable supply of granite for potential future restoration projects. In the United Kingdom, projects like the Cornwall and West Devon Mining Landscape UNESCO World Heritage Site demonstrate how abandoned mining sites can be repurposed for tourism, education, and ecological restoration, contributing to local economies while conserving heritage assets [23,24]. Similarly, in Germany, the Ruhr region's transformation from a coal mining hub to a cultural and creative landscape illustrates the potential for adaptive reuse to foster social cohesion and economic diversification in post-industrial contexts [25].…”
Section: Introductionmentioning
confidence: 99%
“…Sample processing and analysis was performed in an ISO 9001accredited laboratory. No reference material exists for metal concentrations in expanded polystyrene but aqua regia digestion of sediment using the same protocol has been validated with in-house and independent reference sediments and soils (Braungardt et al, 2020;Turner, 2022). All digests and extracts were analysed by ICP-MS in triplicate, with relative standard deviations below 20 % in all cases and below 10 % in most cases.…”
Section: Quality Control and Assurance And Data Processingmentioning
confidence: 99%
“…Successful examples all around the world have shown that former mining areas can be reused to provide social, ecological, and economic benefits [13,57]. Some mines have become touristic attraction points (Kansas, Texas, USA; Wieliczka, Poland), public parks (Konya, Turkey; Lawrence, MA, USA), stadiums (Braga, Portugal), solar power plants (Senftenberg, Germany) or UNESCO sites (Rosas mines in Sardinia-Italy, Almaden Mining Park in Spain, Falun Mine in Sweeden, Cornwall and West Devon in the UK) [13,[58][59][60][61]. But for these transformations to take place, large projects approved by authorities and supported by governments need to be considered.…”
Section: Revitalization Opportunities For Future Development Pathsmentioning
confidence: 99%